National High School Exam (ENEM): Mathematical content more addressed and its difficulties (Research, Society and Development, 2021)
The National High School Exam (ENEM) has become one of the main means of entry to higher education. Mathematics has an influence on the final average, and it is elaborated according to the contents that must be addressed throughout basic education. In this sense, the study aimed to analyze and describe which content is most addressed, what are the difficulties students face when faced with these Mathematics issues present in the ENEM tests, thus proposing strategies to minimize these difficulties. This is a descriptive, exploratory and applied study, in which, initially the exams from 2012 to 2018 of ENEM were analyzed, in which the questions were quantified by attributing their respective contents. Then, questionnaires (pretest) were applied to students in the 3rd year classes of the Federal Institute of Piauí (IFPI) Cocal campus and the Deputado Pinheiro Machado High School, which had 7 questions. Subsequently, an intervention was held on the subject most addressed in ENEM. After this intervention was applied post-test with a total of 8 questions. Analyzing the evidence, it was found that the most addressed content was statistics, in which 70 questions were quantified. With the pretest, students attributed the concept of statistics correctly but failed to interpret most of the questions. After the intervention and after the post-test students performed better, the fact that has been proven by performance in the resolutions of the issues. Through the study, it is concluded that the students have difficulties, as well as the interpretation and understanding of graphs and tables.